2017
DOI: 10.21276/aimdr.2017.3.2.me2
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Thrombocytopenia during Pregnancy & Its Effect on Pregnancy & Neonatal Outcome

Abstract: Background: To study the Prevalence of thrombocytopenia during pregnancy and its effect on pregnancy and neonatal outcome. Methods: It was a prospective one year study of pregnancy with thrombocytopenia. The cause of thrombocytopenia and feto-maternal outcomes in pregnancy with thrombocytopenia was studied. Results: Among 1450 deliveries, total 137 women were having thrombocytopenia in third trimester. The commonest etiology was gestational thrombocytopenia (61%). Thrombocytopenia due to severe preeclampsia an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(27 citation statements)
references
References 7 publications
5
18
0
Order By: Relevance
“…Many reports observed higher rates of preterm deliveries in patients with moderate to severe thrombocytopenia. 4,[6][7][8]11 Our study also had a similar finding.…”
Section: Fig 1: Severity Of Thrombocytopenia According To Etiologiessupporting
confidence: 87%
See 2 more Smart Citations
“…Many reports observed higher rates of preterm deliveries in patients with moderate to severe thrombocytopenia. 4,[6][7][8]11 Our study also had a similar finding.…”
Section: Fig 1: Severity Of Thrombocytopenia According To Etiologiessupporting
confidence: 87%
“…Several studies reported similar incidence. [6][7][8] Presence of medical and obstetric risk factors did not have any influence on maternal and neonatal outcome in these patients. This finding is similar to Nisha et al study.…”
Section: Fig 1: Severity Of Thrombocytopenia According To Etiologiesmentioning
confidence: 70%
See 1 more Smart Citation
“…6 cases of caesarean section wound gape where one underwent exploratory laparotomy is seen in our study. 9,11,12 The study by Pallavi et al showed 1% cases and that of Sumathy et al shows that 0.5% case of incisional site oozing. 9,11 1 case of vaginal hematoma (2.17%) is seen which is similar to study by Pallavi et al having 1 case (2.5%) of episiotomy hematoma and Arora et al reported 5 (3.6%) cases of wound hematoma.…”
Section: Discussionmentioning
confidence: 98%
“…In our study the prevalence was 43.7%. Prevalence of gestational thrombocytopenia was 64.2% in a study conducted by Singh Nisha et al in 2012 15 . There were 74.7% cases of mild thrombocytopenia, 17.9% of moderate and 7.4% were thrombocytopenia.…”
Section: Jmscr Vol||06||issue||01||page 32522-32528||january 2018mentioning
confidence: 92%